Self-Awareness Dimension of Emotional Intelligence: A Predictor of Managerial Effectiveness - Vyas, Priyanka; Yadav, Ravindra; Sharma, Jyoti (International Journal of Computer Sciences and Engineering, 2025)
The success of any organization depends largely on tapping the potential in the workplace who are committed to organizational goals, service quality, commendable behaviour and formulate the tasks according to the plans. Maxwell (1995) stated that many organizations fail because of they were not able to tap the potentials. The only reward they give their employees is a pay cheque. But successful organizations develop the relationship between employer and employee. Managers should deal with the challenging issues with subsist in Employees State Insurance Corporation. For subordinates or employees to commit themselves to the company’s vision, mission and goals, top level management promote a productivity culture in organization. In Employees State Insurance Corporation, they have significant roles which challenge for managerial effectiveness and direct job performance. It is apparent that evaluating the quality of performance of any establishment is an essential part to meet the beneficiaries’ needs and expectations. Managerial effectiveness in terms of realistic evaluation facilitate organizational development, analysing the system, implementation, transformation, building healthy work relationship to meet the needs of their clients through emphasizing the strengths and weaknesses. The managerial effectiveness is best measured in terms of actions taken with the objectives of promoting improvement and directions in ESIC. It is the process by which the organizational management system undergoes subsequent evaluation initiated by the managers, mechanisms to strategically run the organizations for efficiency and productivity to establish good camaraderie among employees of ESIC. In this study self-awareness a dimension of emotional intelligence determined to examine the impact on managerial effectiveness. For this study 400 employees of ESIV were chosen on the basis of purposive sampling